HAK DAN KEWAJIBAN WARGA NEGARA DALAM PERSPEKTIF AL-QUR’AN - hatnima hannum; Anwar sidik (Civic Edu : Jurnal Pendidikan Kewarganegaraan, 2026)
This study examines the concepts of rights and obligations of citizens from a Qur’anic perspective. The Qur’an presents a comprehensive and balanced framework in which rights and obligations are closely interconnected and cannot be separated. Every individual is granted fundamental rights, including the right to life, justice, equality, and human dignity. At the same time, individuals are required to fulfill their obligations, such as maintaining moral integrity, promoting social harmony, and showing responsibility toward others. The principle of justice (‘adl) plays a central role in regulating this relationship, ensuring fairness and preventing oppression. This research employs a qualitative descriptive method by analyzing relevant Qur’anic verses and interpretations. The findings reveal that the Qur’an emphasizes balance, proportionality, and accountability in human interactions and social relations today. Furthermore, it highlights that rights must be exercised responsibly and obligations fulfilled sincerely to achieve a just and harmonious society for all members of society.